A self-assembled liquid crystal honeycomb of highly stretched (3-1-1)-hexagons. Issue 1 (4th December 2019) - Scholte, Alexander; Hauche, Sebastian; Wagner, Matthias; Prehm, Marko; Poppe, Silvio; Chen, Changlong; Liu, Feng; Zeng, Xiangbing; Ungar, Goran; Tschierske, Carsten
Abstract : Polyphilic molecules form a new highly stretched liquid crystal honeycomb when the attached chains are too long for a regular hexagonal honeycomb and too short for a lamellar structure. Abstract : A new liquid crystalline honeycomb phase is reported, containing highly stretched giant hexagonal cells with two opposing walls spanned by three consecutive end-to-end H-bonded rods, the (3-1-1) hexagons.